2010
DOI: 10.1007/jhep02(2010)025
|View full text |Cite
|
Sign up to set email alerts
|

Finite top quark mass effects in NNLO Higgs boson production at LHC

Abstract: We present next-to-next-to-leading order corrections to the inclusive production of the Higgs bosons at the CERN Large Hadron Collider (LHC) including finite top quark mass effects. Expanding our analytic results for the partonic cross section around the soft limit we find agreement with a very recent publication by Harlander and Ozeren \cite{Harlander:2009mq}.Comment: 15 page

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
169
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(177 citation statements)
references
References 44 publications
7
169
0
Order By: Relevance
“…At NLO, the approximation m t ≫ M H for the contribution of the top quark in the loop is rather good for Higgs masses below the tt threshold, M H < ∼ 340 GeV, in particular when the full quark mass dependence of the leading order cross section σ LO exact is taken into account [27]. At NNLO, this approximation for the top quark contribution seems also to be accurate as studies of the effect of a finite m t value in expansions of M H /(2m t ) have shown a difference below the percent level with respect to the EFT calculation for M H 300 GeV [78][79][80][81].…”
Section: The Use Of An Effective Theory Approachmentioning
confidence: 99%
“…At NLO, the approximation m t ≫ M H for the contribution of the top quark in the loop is rather good for Higgs masses below the tt threshold, M H < ∼ 340 GeV, in particular when the full quark mass dependence of the leading order cross section σ LO exact is taken into account [27]. At NNLO, this approximation for the top quark contribution seems also to be accurate as studies of the effect of a finite m t value in expansions of M H /(2m t ) have shown a difference below the percent level with respect to the EFT calculation for M H 300 GeV [78][79][80][81].…”
Section: The Use Of An Effective Theory Approachmentioning
confidence: 99%
“…in the formal limit M h → 0. For Higgs boson masses considered here this approximation approaches the exact result to high accuracy [15][16][17][18]. We have cross checked our implementation against the results implemented in [20] in certain limits.…”
Section: Numerical Setupmentioning
confidence: 85%
“…[6] we have decided to consider the forward scattering amplitudes and evaluate those imaginary parts which involve a cut of the Higgs boson line. In a first step we generate the diagrams and apply subsequently the asymptotic expansion in the limit 2 M 2 t ≫ŝ, M 2 H , implemented in two independent programs.…”
Section: Outline Of the Calculationmentioning
confidence: 99%
“…[5,7] an expansion in x = M 2 H /ŝ has been performed whereas in Ref. [6] the full x-dependence is kept. Apart from that the results of [5,7] and [6] agree.…”
Section: Outline Of the Calculationmentioning
confidence: 99%
See 1 more Smart Citation